A hierarchical optimization and design of double Kalina Cycles for waste heat recovery. (15th March 2021) - Zhuang, Yu; Zhou, Congcong; Dong, Yachao; Du, Jian; Shen, Shengqiang
Abstract: With the coming of global energy crisis, the optimization of waste heat recovery is crucial for improving the energy utilization efficiency. In waste heat recovery, complex interactions between cycle parameters and multiple cycle structures are often neglected. To overcome this drawback and improve heat recovery efficiency, a novel hierarchical framework is proposed for the optimization of double Kalina Cycles (D-KC) considering the systematic design of parameters and coupling structure. The coupling structure in such a heat recovery system include the heat-exchange matches among multiple cycles as well as those between cycles and the heat source. The proposed modeling method combines the pinch-based extended Duran-Grossmann model and the expanded transshipment model to obtain the optimal configurations with the successive objective of maximizing the power output and maximizing outlet temperature of the heat source. Compared with that of two Kalina Cycles in cascade (C-KC) and basic Kalina Cycle (B-KC), the power output of D-KC is increased by 12.55% and 34.89%, respectively in the case study; while the exergy efficiency of D-KC is improved by 11.6% and 8.49% compared with that of C-KC and B-KC, respectively. The levelized cost of electricity of D-KC is similar to that of C-KC, and both of them are slightly higher than that of B-KC, due to the fact that more devices, especially the costly turbines, are needed in the multiple cycles. Graphical abstract: Image 1 Highlights: A framework of design for coupling structure of multiple Kalina Cycles is proposed. The coupling structure considers heat exchange matches between cycles and heat source. A hierarchical model is established for optimization of double KCs. The cycle parameters and coupling structures are optimized simultaneously. More power output, larger exergy efficiency and similar economic cost are obtained.